Cloning, nucleotide sequence, and transcriptional analyses of the gene encoding a ferredoxin from Methanosarcina thermophila. - Clements, A P (1992)
A mixed 17-mer oligonucleotide deduced from the N terminus of a ferredoxin isolated from Methanosarcina thermophila was used to probe a lambda gt11 library prepared from M. thermophila genomic DNA; positive clones contained either a 5.7- or 2.1-kbp EcoRI insert. An open reading frame (fdxA) located within the 5.7-kbp insert had a deduced amino acid sequence that was identical to the first 26 N-terminal residues reported for the ferredoxin isolated from M. thermophila, with the exception of the initiator methionine. fdxA had the coding capacity for a 6,230-Da protein which contained eight cysteines with spacings typical of 2[4Fe-4S] ferredoxins. An open reading frame (ORF1) located within the 2.1-kbp EcoRI fragment also had the potential to encode a 2[4Fe-4S] bacterial-type ferredoxin (5,850 Da). fdxA and ORF1 were present as single copies in the genome, and each was transcribed on a monocistronic mRNA. While the fdxA- and ORF1-specific mRNAs were detected in cells grown on methanol and trimethylamine, only the fdxA-specific transcript was present in acetate-grown cells. The apparent transcriptional start sites of fdxA and ORF1, as determined by primer extension analyses, lay 21 to 28 bases downstream of sequences with high identity to the consensus methanogen promoter.